Spatial and Social Changes in Alun-Alun Semarang 1967-1972 as a Learning Resource - Arianto, Risa Andi (Universitas Negeri Semarang, 2017)
Semarang Square changed by adding commercial buildings such as markets and markets, including Yaik Johar, who took land from Semarang Square, which caused many factors. The government played a role in climate policy and the creation, in addition to other factors, such as the role of the party in power, impact orientation of development, and modernization of traditional markets.